Physalin H, physalin B, and isophysalin B suppress the quorum-sensing function of Staphylococcus aureus by binding to AgrA - Yamaguchi, Junpei; Manome, Teruhisa; Hara, Yasumasa; Yamazaki, Yuriko; Nakamura, Yuumi; Ishibashi, Masami; Takaya, Akiko (Frontiers in Pharmacology, 2024)
The virulence of Staphylococcus aureus, including methicillin-resistant S. aureus (MRSA), depends on the expression of toxins and virulence factors controlled by the quorum-sensing (QS) system, encoded on the virulence accessory gene regulator (agr ) locus. The aim of this study was to identify a phytochemical that inhibits Agr-QS function and to elucidate its mechanism. We screened 577 compounds and identified physalin H, physalin B, and isophysalin B--phytochemicals belonging to physalins found in plants of the Solanaceae family--as novel Agr-QS modulators. Biological analyses and in vitro protein-DNA binding assays suggested that these physalins suppress gene expression related to the Agr-QS system by inhibiting binding of the key response regulator AgrA to the agr promoters, reducing the function of hemolytic toxins downstream of these genes in MRSA. Furthermore, although physalin F suppressed gene expression in the Agr-QS system, its anti-hemolytic activity was lower than that of physalins H, B, and isophysalin B. Conversely, five physalins isolated from the same plant with the ability to suppress Agr-QS did not reduce bacterial Agr-QS activity but inhibited AgrA binding to DNA in vitro. A docking simulation revealed that physalin interacts with the DNA-binding site of AgrA in three docking states. The carbonyl oxygens at C-1 and C-18 of physalins, which can suppress Agr-QS, were directed to residues N201 and R198 of AgrA, respectively, whereas these carbonyl 1Physalins suppress quorum sensing in S. aureus oxygens of physalins, without Agr-QS suppression activity, were oriented in different directions.Next, 100-ns molecular dynamics simulations revealed that the hydrogen bond formed between the carbonyl oxygen at C-15 of physalins and L186 of AgrA functions as an anchor, sustaining the interaction between the carbonyl oxygen at C-1 of physalins and N201 of AgrA. Thus, these results suggest that physalin H, physalin B, and isophysalin B inhibit the interaction of AgrA with the agr promoters by binding to the DNA-binding site of AgrA, suppressing the Agr-QS function of S. aureus. Physalins that suppress the Agr-QS function are proposed as potential lead compounds in the anti-virulence strategy for MRSA infections.